Perceptions of discrimination in athletic training education programs - Gilette, Charles J. (My University, 2000)
Sexual harassment and mistreatment of students in medical school and allied health programs have been well dccumented. The student athletic trainer - perceptions of treatment questionnaire was used to determine the perceptions of Ss in athletic training education programs (ATEP). The sample included 260 Ss (93 male and 167 female; age 21.8 +_ 3.24 yrs, 19-44) enrolled in O.TEP (2.37 yrs -t .996 yrs; accumulated hours 880.75 f 45 1.1 1,56-2500hrs). R.eturn rate was 47.6% from Ss surveyed in accredited ATEP's. Ss were asked about self and peer perceived discrimination. Results indicated that 60.4% (male = 66.7%, female = 56.9%) of the Ss felt they were victims of discrimination. Areas in which Ss perceived self-discrimination included: offensive language (44.2%), exclusion on the basis of gender (3 1.2%), sexual humor (25%), and unwanted sexual advances (3.8%). Results from perceived discrimination of peers indicated that 63.8% (male = 72%, female = 60.5%) of the Ss thought their peers were victims of discrimination. Areas in which Ss perceived discrimination of peers included: offensive language (56.9%), exclusion on the basis of gender (3 1.5%), sexual humor (35.4%), and unwanted sexual advances (1 1.5%).
Keywords: Sexual harassment in education; Sex discrimination in education; Athletic trainers - Attitudes; Athletic trainers - Education (Higher) - United States